2019
DOI: 10.20964/2019.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Jet electrodeposition Nickel Coating on TC4 Alloy Prepared by Selective Laser Melting

Abstract: In order to solve the problems of poor surface wear resistance and low hardness of titanium alloy materials formed by selective laser melting (SLM) technology, a new method of preparing bright nickel protective coating by jet electrodeposition was proposed in this paper. The surface morphology of the coatings was characterized by field emission scanning electron microscopy. The microhardness tester, scratch tester, and friction and wear tester were used to analyze the adhesion, hardness, and wear resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Comparing several different heat treatment processes, research shows that the strength and hardness of SLM formed TC4 alloy samples have been improved to a certain extent after heat treatment. After 8008C/2h annealing treatment, the TC4 alloy sample has the lowest residual stress value of 43 MPa, which best matches the strong plasticity properties (Huang, 2018). Ti17 titanium alloy not only has the characteristics of α þ β type alloy, but is also a transition type alloy rich in β stabilizing elements.…”
Section: Surface Integrity Of Metal Additive Parts 21 Surface Integri...mentioning
confidence: 56%
“…Comparing several different heat treatment processes, research shows that the strength and hardness of SLM formed TC4 alloy samples have been improved to a certain extent after heat treatment. After 8008C/2h annealing treatment, the TC4 alloy sample has the lowest residual stress value of 43 MPa, which best matches the strong plasticity properties (Huang, 2018). Ti17 titanium alloy not only has the characteristics of α þ β type alloy, but is also a transition type alloy rich in β stabilizing elements.…”
Section: Surface Integrity Of Metal Additive Parts 21 Surface Integri...mentioning
confidence: 56%
“…This is due to the characteristic “tip discharge” effect of jet electrodeposition that will make the nickel ions tend to reduce to atoms at the peak where the discharge is easier, resulting in a thicker coating at the peak and thinner coating at the trough. 21 The uneven thickness of the coating is very harmful to the coating structure and adhesion when the internal stress is released, and leads to the easy generation of micro-cracks and can even lead to the rupture of the coating. Figure 8 shows a schematic illustration of the sand blasting and surface coating processing.…”
Section: Resultsmentioning
confidence: 99%
“…Jet electrodeposition has several advantages such as low processing costs, high deposition current density, high selectivity, high velocity, high efficiency and ability to plate thick composite coatings with fine grains [4][5][6], which can be used to prepare excellent properties with composite coating and enhance the local surface of metallic parts. Shen et al [7] found that the multilayered structure nickel coating using jet electrodeposition can further improve corrosion resistance and better protect the NdFeB material.…”
Section: Introductionmentioning
confidence: 99%